2008
DOI: 10.1038/mt.2008.200
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Pseudouridine Into mRNA Yields Superior Nonimmunogenic Vector With Increased Translational Capacity and Biological Stability

Abstract: In vitro–transcribed mRNAs encoding physiologically important proteins have considerable potential for therapeutic applications. However, in its present form, mRNA is unfeasible for clinical use because of its labile and immunogenic nature. Here, we investigated whether incorporation of naturally modified nucleotides into transcripts would confer enhanced biological properties to mRNA. We found that mRNAs containing pseudouridines have a higher translational capacity than unmodified mRNAs when tested in mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,156
6
30

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,350 publications
(1,346 citation statements)
references
References 26 publications
36
1,156
6
30
Order By: Relevance
“…negatively affects its translation, implying that stronger TiDC activation could be obtained using "modified" mRNA that does not trigger PRRs (40)(41)(42). If PRRs are triggered, the effects observed in this study may be due to the delivery of mRNA rather than the delivery of TriMix mRNA.…”
Section: Cd8amentioning
confidence: 79%
“…negatively affects its translation, implying that stronger TiDC activation could be obtained using "modified" mRNA that does not trigger PRRs (40)(41)(42). If PRRs are triggered, the effects observed in this study may be due to the delivery of mRNA rather than the delivery of TriMix mRNA.…”
Section: Cd8amentioning
confidence: 79%
“…28 A modified nucleoside 59-triphosphate solution was used, in which pseudouridine-59-triphosphate (pseudo-UTP) and 5-methylcytidine-59-triphosphate (5-methyl-CTP) were substituted for UTP and CTP, respectively. 29 After transcription, uncapped RNA was purified using an RNeasy kit (Qiagen, Hilden, Germany) and a 59 cap structure and 39-poly(A) tail were added using the mScript kit. Transcripts were then repurified and quantified, and the success of the poly(A) tailing reaction was confirmed by agarose gel electrophoresis.…”
Section: Mrna Synthesismentioning
confidence: 99%
“…Two of the modified nucleosides, S2U and pseudouridine, seem to reduce detection by RIG-I and PKR as well [33,87]. Additionally, in 2008, pseudouridine was shown to increase mRNA translation capacity, by improving the overall stability of mRNA and avoiding PKR recognition [88,89]. In the same vein, Kormann et al indicated that replacement of 25% uridine and cytidine with s2U and m5C substantially reduced binding to PRRs and decreased innate immune activation, leading to an increased protein expression in vitro and in vivo [90].…”
Section: Modifying the Mrnamentioning
confidence: 99%